Mengatasi Pecandu Game Online Melalui Dakwah Online - Nurrohman Zulkarnain; Leni Yanti (STAI Bumi Silampari, 2021)
The purpose of this literature review is to find out the phenomenon of da'wah in internet media, especially in dealing with the millennial generation who are addicted to online games. As well as solutions to overcome these problems through online da'wah using various methods contained in the Qur'an surah al-Nahl: 125.